1989
DOI: 10.1002/etc.5620080407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contaminants on the frequencies of allozymes in populations of the central stoneroller

Abstract: Allele and genotype frequencies for allozymes of phosphoglucomutase (PGM) differed significantly between populations of the central stoneroller (Campostoma anomalum, Rafinesque) collected from sites above and below impact from industrial activities. The frequencies of the PGM‒A allele and PGM‒AA and PGM‒AB genotypes were significantly less in populations of stoneroller minnows collected from impacted sites than in populations upstream of impact. Stonerollers with these sensitive PGM genotypes and stonerollers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 14 publications
1
46
1
Order By: Relevance
“…This result is in line with the findings of Theodorakis and Shugart (1997) as well as Yap et al (2004) where measures of genetic diversity indicated that the contaminated sites were more similar to one another than to the non-contaminated sites. Many researchers and ecotoxicologists had suggested that monitoring changes in population genetic structures by allozyme analysis is a valuable and useful population-level biomarker of heavy metal contamination (Lavie and Nevo 1986;Ben-Shlomo and Nevo 1988;Gillespie and Guttman 1989;Diamond et al 1989;Yap et al 2004;Yap and Tan 2007). In addition, the dendrogram drawn based on Nei's (1978) genetic identity values was in agreement with the SLBGMED dendrogram of heavy metals in the non-resistant fraction of the sediments obtained by SET (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This result is in line with the findings of Theodorakis and Shugart (1997) as well as Yap et al (2004) where measures of genetic diversity indicated that the contaminated sites were more similar to one another than to the non-contaminated sites. Many researchers and ecotoxicologists had suggested that monitoring changes in population genetic structures by allozyme analysis is a valuable and useful population-level biomarker of heavy metal contamination (Lavie and Nevo 1986;Ben-Shlomo and Nevo 1988;Gillespie and Guttman 1989;Diamond et al 1989;Yap et al 2004;Yap and Tan 2007). In addition, the dendrogram drawn based on Nei's (1978) genetic identity values was in agreement with the SLBGMED dendrogram of heavy metals in the non-resistant fraction of the sediments obtained by SET (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Sensitivity of allozymes to environmental stress seemed to reflect the adaptive nature of the individuals (MORAGA et al 2002). Anthropogenic factors such as pollution appeared to favour the selection of individuals with particular genetic composition within the fish populations through differential survival of the species (THORPE et al 1981;SMITH et al 1983;GILLESPIE & GUTTMAN 1989;DUAN et al 2001). Moreover, KOPP et al (1994) reported that genotypes that survived an exposure to pollution or salinity can represent the most tolerant individuals in a stressful environment.…”
Section: Kétesso -mentioning
confidence: 94%
“…Moreover, KOPP et al (1994) reported that genotypes that survived an exposure to pollution or salinity can represent the most tolerant individuals in a stressful environment. CHAGNON & GUTTMAN (1989) and GILLESPIE & GUTTMAN (1989) reported that the degree of genetic variation maintained by a population can be the proof of its ability to survive a future environmental decay. The observed differences in genetic diversity between populations from a disturbed environment with varying degrees of stress may also be the result of other factors.…”
Section: Kétesso -mentioning
confidence: 98%
“…Chagnon & Guttman, 1989a;Duan et al, 2000;Theodorakis, 2003), and (iv) allozyme loci may be good bioindicators for metal toxicants as these may have direct effects on enzyme structure and function (e.g. Chagnon & Guttman, 1989a, b;Gillespie & Guttman, 1989). Hence, allele or genotype frequencies may be associated with the degree of pollution in any given environment (Gillespie & Guttman, 1999;D'Surney, Shugart & Theodorakis, 2001).…”
Section: Introductionmentioning
confidence: 99%